EVALUASI MANAJEMEN KURIKULUM DI SMK WERDHI SILA KUMARA SILAKARANG - Parwati, Ni Putu Yuniarika; Cahayani, Ni Luh Putu (LP2M IKIP PGRI Bali, 2019)
This study aims to determine the implementation of curriculum management at SMK Werdhi Sila Kumara Silakarang in Singapadu Kaler Village. In this study the approach used is management-oriented evaluation approach (EBM) with the evaluation model is the CIPP model. Data collection was carried out using questionnaires, interviews, and documentation. Based on the quantitative analysis conducted, it is known that the implementation of curriculum management from planning, implementing, evaluating, and supervising is included in the very effective category. Through planning, the principal of SMK Werdhi Sila Kumara Silakarang together with the Curriculum Development Team compiled a curriculum program starting from the semester program, annual program, syllabus, Learning Implementation Plan, learning materials and learning media needed for one school year. While in organizing, the school prepares a curriculum that is relevant to national education goals and adapted to regional needs. These programs are then well introduced and implemented by teachers and students. In order for these programs to be implemented well, supervision and evaluation are carried out.